Southern Sierra Critical Zone Observatory and Kings River Experimental Watersheds: A Synthesis of Measurements, New Insights, and Future Directions. Issue 1 (29th November 2018) - O'Geen, Anthony (Toby); Safeeq, Mohammad; Wagenbrenner, Joseph; Stacy, Erin; Hartsough, Peter; Devine, Scott; Tian, Zhiyaun; Ferrell, Ryan; Goulden, Mike; Hopmans, Jan W.; Bales, Roger
Abstract : Core Ideas: Water quality and stream flow have temporal and spatial trends in response to variable climate. Our work reveals how Sierra Nevada forests responded to and recovered from multiyear drought. Regolith thickness trends reveal water storage capacity differences with elevation. Monitoring shows deep‐water changes via plant utilization or capillary flow during drought. Sensor networks within the Southern Sierra Critical Zone Observatory (SSCZO) and Kings River Experimental Watersheds (KREW) document changes in the water cycle spanning the west slope of the southern Sierra Nevada in California. The networks were established to document water dynamics throughout the critical zone spanning profile, hillslope, catchment, and watershed scales at key locations that reflect systematic differences in bioclimatic conditions imposed by a strong elevation gradient. The critical zone observatory attempts to constrain the hydrologic budget via representative measurements of streamflow, eddy flux covariance, snow depth, meteorological conditions, and water content and water potential in soil and deep regolith. These measurements reveal the complexity of interactions among all aspects of the water balance (runoff, storage, evapotranspiration [ET], and precipitation) through daily, seasonal, and annual timescales. Multiyear drought, catastrophic wildfires, insect outbreaks, and disease have caused widespread tree mortality in the Sierra Nevada. These disturbances offer a window into the future for this region, which is expected to undergo significant change in response to global warming. This hydrological observatory provides valuable hydrometric attributes and fluxes across the stream–groundwater–vadose zone–soil–vegetation–atmosphere continuum.